2011
DOI: 10.1007/s12239-011-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of valve spring surge amplitude using the variable natural frequency and the damping ratio

Abstract: Internal vibration of the valve spring is a critical factor in determining the dynamic characteristics of highspeed valve train systems. Because precise prediction of the spring surge amplitude is a difficult problem, especially for nonlinear variable-pitch springs, the development stage requires a process of trial and error. In the present study, a new method that considers the variable natural frequency and variable damping ratio is proposed to predict the spring surge amplitude. First, the change in the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…By using this method, the dynamic equation is transformed from a partial differential equation to a set of ordinary differential equations. However, these equations have not considered the internal damping of the spring which plays an essential role in accurately estimating the dynamic vibration of spring [25,36]. Therefore, a viscous damping term is added into Eq.…”
Section: High-speed Dynamic Spring Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…By using this method, the dynamic equation is transformed from a partial differential equation to a set of ordinary differential equations. However, these equations have not considered the internal damping of the spring which plays an essential role in accurately estimating the dynamic vibration of spring [25,36]. Therefore, a viscous damping term is added into Eq.…”
Section: High-speed Dynamic Spring Modelmentioning
confidence: 99%
“…In the vehicle suspension system, the suspension springs are usually grounded for the purpose of mounting [23,24]. In addition, valve springs are intentionally designed to have varied spring pitch for the purpose of reduction of spring surge [25]. Moreover, unique spring designs, like beehive spring, conical spring and barrel spring, are all against the assumption of a constant coil diameter [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural frequency is referred to as the frequency at which the structure will vibrate once displaced and quickly released [27]. As the damping ratio determines the size of amplitude [28], so it is a common consideration for tool designing. Therefore, this research investigated the damping impact on the 1-dimensional (1D) ultrasonic-assisted cutting tool.…”
Section: Introductionmentioning
confidence: 99%
“…It is also showed that amplitude‐dependent damping characteristics is based on field measurement . The fundamental natural frequency and the damping ratio decrease with acceleration amplitude . Taken as a thin rotating shell, a cooling tower has its unique configuration and material attributes, so the actual damping ratio must be smaller as compared with the high‐rise buildings.…”
Section: Introductionmentioning
confidence: 99%